A Murder of quality - Le Carré, John 1931-2020 (Middlesex Penguin books, 1964)
George Smiley, the cleverest and most self-effacing man in Security, investigates a murder in one of England's leading public schools - a murder that was forecast by the victim.
Reimpressions: 1982